Exploring New Conceptualisations of Old Problems: Researching and Reorienting Teaching in Indigenous Studies to Transform Student Learning - Page, Susan (The Australian Journal of Indigenous Education, 2014)
Indigenous Studies can be both exciting and challenging for teachers and students. This article will examine how an existing learning theory can be harnessed to help teachers better understand these challenges and manage some frequently seen student behaviours. Much of the discussion in Indigenous Studies pedagogy to date has focused on the curriculum and what we should be teaching, with a growing body of literature, for example, related to the inclusion of Indigenous Knowledges. However, there is less written about how students learn in Indigenous Studies. Drawing on the notion of the Cultural Interface and the ‘zone of proximal development’ to highlight the complexity of Indigenous Studies classrooms as a site of necessary struggle for students, the article considers possibilities for reconceptualising and reorienting teaching. The paper explores using the threshold concepts framework to gather evidence about how students learn or indeed don't learn, in Indigenous Studies. Threshold concepts are key ideas, critical to mastering discipline specific knowledge, which facilitate students’ ability to think like a discipline experts.